The UV-B stimulon of the terrestrial cyanobacterium Nostoc commune comprises early shock proteins and late acclimation proteins. - Ehling-Schulz, M; Schulz, S; Wait, R; Görg, A; Scherer, S (2002)
The UV-B and desiccation-tolerant terrestrial cyanobacterium Nostoc commune was grown under defined UV irradiation. Proteome changes were monitored in the membrane and the cytosolic and the extracellular fractions. Tools were developed to separate stress-triggered from growth stage-dependent changes. UV-B changed the relative cellular concentration of 493 out of 1,350 protein spots at least by a factor of three, rendering the UV-B stimulon of N. commune the most complex one described so far. It comprises two different parts: an early shock response influencing 214 proteins and a late acclimation response involving 279 proteins. The shock response comprised many membrane or membrane-associated proteins, whereas the acclimation response mainly changed cytosolic proteins. Most of the shock-induced changes were transient and did not overlap with the acclimation response. In the extracellular fraction, UV irradiation induced superoxide dismutase and the water stress protein. In total, 27 intracellular, UV-B-induced proteins were partially sequenced by electrospray ionization tandem mass spectrometry. Three functional classes were identified: proteins involved in lipid metabolism, in carbohydrate metabolism and in regulatory pathways. About 50% of the sequenced proteins were homologous to cyanobacterial database entries with un-known function. Interestingly, all of these proteins belong to the UV-B acclimation response. We conclude that the UV-B shock response and the UV-B acclimation response represent two completely different and remarkably complex strategies of N. commune to protect itself against UV-B radiation in its natural environment.